Assembling the Anthropocene: How do museums engage with the global environmental crisis through objects, exhibitions and museum work? - Ãžórsson, Bergsveinn (Tidsskrift for kulturforskning, 2020)
The Anthropocene is a geological concept proposing that Earth has entered a new geological epoch, a period driven by the impact of human activity on the planet. The decisive influences humans have had on the planet are uncontested: growing concentration of carbon dioxide in the atmosphere, accumulation of trash and pollution, unsustainable natural resource extraction, urbanisation and intensive agricultural activity are among the impacts that will undoubtedly leave a permanent mark in the geological record for unforeseeable future.